Business strategy analysis to improve competitiveness sustainable competitiveness in Bakpia AA Business in Gunung Sugih Lampung Tengah - Muhammad Fauzi Yazid; Vonny Tiara Narundana (Institute of Computer Science (IOCS), 2024)
The problem of this research is related to the low competitiveness of regional speciality food MSMEs in Lampung Province, mainly indicated by the decline in revenue of Bakpia AA in the past 5 years. The purpose of the study was to identify business strategies to increase competitiveness and sustainability in the Bakpia AA business in Gunung Sugih, Central Lampung. This study used SWOT analysis with six respondents involved in the operation and marketing of Bakpia AA. The results showed that Bakpia AA business in Gunung Sugih Central Lampung is in Quadrant III, indicating great opportunities but also some weaknesses in the business environment. Strategies for developing Bakpia AA's competitiveness and sustainability include limited technology investment to improve operational efficiency, online expansion through platforms such as Tokopedia/Shopee, partnership with local stores to maintain product quality, diversification of suppliers and products, utilisation of bazaars as promotional media, cooperation with nearby companies, delivery facilities and integration with online food applications, and utilising the unique location near offices as a competitive advantage.